Migrants’ health policies and access to health care in Portugal within the European Framework - Casquilho-Martins, I.; Ferreira, S. (Societies, 2022)
Migratory flows have a specific influence in the European and Portuguese demographic context. Societies’ commitment to ensure fundamental rights of all citizens and migrants includes the promotion of health. This study aims to describe migrants’ health policies and access to the health system in Portugal within the European framework. We carried out a mixed methods approach, analyzing health policies in European Union countries and public health key indicators from statistical secondary data collected from Eurostat and Migrant Integration Policy Index. This data was complemented with a survey applied to immigrants living in Portugal. Portugal is a European country known for its favorable immigrant integration policies and has developed access to the health care system. However, our study has shown that greater investment is needed to overcome limitations or social inequalities which inhibit migrants’ access. Additionally, we sought to present a comparative analysis between Portugal and European Union countries, which can contribute to improve health systems within the current crisis.